Optimization of Pb(II) Metal Adsorption on Pomelo Peel Biosorbent by Immobilization in Ca-Alginate - Rasyid, Zulfa Wulandari; Paramita, Vita (Vocational College of Universitas Diponegoro, 2022)
Industrial wastewater is a source of water pollution that dominates today. Wastewater is known to cause damage to the environment, health and threatens the availability of clean water. Industrial wastewater is a problem because it contains a lot of dangerous heavy metals, one of which is Lead or Pb(II).' Adsorption technology has become one of the most exciting technologies because of its good performance. Adsorption media currently popular for the study is adsorption using agricultural waste. One of the agricultural wastes that can be used as biosorbent is grapefruit peel (Citrus maxima). The functional groups in grapefruit peel are ether, pedophilic, carboxyl, carbonyl, and hydroxyl. These functional groups are essential in binding heavy metals from the aquatic environment. In this study, grapefruit peel was modified into a Ca-alginate immobilized biosorbent. The analyzes that will be carried out include the characteristics of the biosorbent, namely the water content and ash content test, the FTIR test to determine the functional groups contained in the biosorbent, the SEM-EDX test to assess the appearance of the biosorbent, as well as analysis of the initial and final levels of Pb(II). Based on the results obtained, the best percentage decrease in Pb(II) levels was obtained with operating conditions of pH 4.7, contact time of 90 minutes, and Pb(II) concentration of 100 mg/L with a percentage decrease in Pb(II) levels of 89%.